The Many Faces of Purpura: Vancomycin-Induced Leukocytoclastic Vasculitis - John A. Zadroga; Vanajakshi Mogulla; Christopher Grant; Djordje Jevtic; Andrew Virata; Igor Dumic (Case Reports in Infectious Diseases)
Leukocytoclastic vasculitis is a rare form of immune-mediated vasculitis that might be caused by infections or autoimmune diseases or might be precipitated by specific medications. We describe a 65-year-old patient, who was receiving vancomycin for a methicillin-sensitive Staphylococcus aureus permacath infection. Vancomycin was chosen due to medication non-adherence and the patient’s desire to receive antimicrobial therapy in conjunction with his scheduled dialysis sessions. The patient’s medical history was notable for untreated hepatitis C infection and end-stage renal disease, requiring hemodialysis three times a week. Vancomycin was administered during dialysis sessions. After one week of therapy, the patient developed bilateral lower extremity purpura. Skin biopsy was suggestive of leukocytoclastic vasculitis with an absence of intravascular thrombi. Serum cryoglobulins were negative, making cryoglobulinemia due to HCV infection unlikely. Following cessation of vancomycin therapy, the rash gradually disappeared with scarring in the form of post-purpuric hyperpigmentation. Despite its widespread use, vancomycin is a rare cause of leukocytoclastic vasculitis. Clinicians should keep in mind a wide range of differential diagnosis of bilateral lower extremity purpura as treatment differs depending on its underlying etiology.